Immunomodulatory action of dietary fish oil and targeted deletion of intestinal epithelial cell PPARδ in inflammation-induced colon carcinogenesis - Monk, Jennifer M. (American Physiological Society, 2012)
The ligand-activated transcription factor peroxisome proliferator-activated receptor (PPAR)-δ is highly expressed in colonic epithelial cells; however, the role of PPARδ ligands, such as fatty acids, in mucosal inflammation and malignant transformation has not been clarified. Recent evidence suggests that the anti-inflammatory/chemoprotective properties of fish oil (FO)-derived n-3 polyunsaturated fatty acids (PUFAs) may be partly mediated by PPARδ. Therefore, we assessed the role of PPARδ in modulating the effects of dietary n-3 PUFAs by targeted deletion of intestinal epithelial cell PPARδ (PPARδ(ΔIEpC)). Subsequently, we documented changes in colon tumorigenesis and the inflammatory microenvironment, i.e., local [mesenteric lymph node (MLN)] and systemic (spleen) T cell activation. Animals were fed chemopromotive [corn oil (CO)] or chemoprotective (FO) diets during the induction of chronic inflammation/carcinogenesis. Tumor incidence was similar in control and PPARδ(ΔIEpC) mice. FO reduced mucosal injury, tumor incidence, colonic STAT3 activation, and inflammatory cytokine gene expression, independent of PPARδ genotype. CD8(+) T cell recruitment into MLNs was suppressed in PPARδ(ΔIEpC) mice. Similarly, FO reduced CD8(+) T cell numbers in the MLN. Dietary FO independently modulated MLN CD4(+) T cell activation status by decreasing CD44 expression. CD11a expression by MLN CD4(+) T cells was downregulated in PPARδ(ΔIEpC) mice. Lastly, splenic CD62L expression was downregulated in PPARδ(ΔIEpC) CD4(+) and CD8(+) T cells. These data demonstrate that expression of intestinal epithelial cell PPARδ does not influence azoxymethane/dextran sodium sulfate-induced colon tumor incidence. Moreover, we provide new evidence that dietary n-3 PUFAs attenuate intestinal inflammation in an intestinal epithelial cell PPARδ-independent manner.